Workforce planning-going beyond the count - Lewis G. Sandy (BMC, 2017)
Abstract Every country struggles with how best to meet the demand for health care services with the available resources. This commentary offers a perspective on the Israeli physician workforce and the analyses of Horowitz et al., which found age and gender differences in physician productivity and career longevity, differences across specialties, and a sizeable fraction of licensed Israeli physicians living abroad. Workforce planning can be subject to data collection and statistical uncertainties, but even more important are the assumptions and forecasts related to demand for services and organizational arrangements for care delivery. Readers should be cautious in analyzing productivity just by counting hours or years worked, and comparisons across countries may not account for differences in the nature of physician work. The question of whether Israel has enough physicians for the future has to go "beyond the count" to looking at the roles of other health professionals, the use of new technologies and new team configurations, and the overall efficiency and effectiveness of health care delivery systems such as hospitals, ambulatory care clinics, and community-based care.